CARACTERIZAÇÃO DE PARÂMETROS AGRONÔMICOS E OPERACIONAIS DA COLHEITA MECANIZADA DA CULTURA DO FEIJÃO (Phaseolus vulgaris L.) - Dalzoto, Mireile (2009)
The beans that each season, in southern Parana, being grown dramatically as a result of the intensification of agricultural mechanization in the harvesting process. The present study aims to identify and characterize the bean crop and the factors that influence the process of mechanical harvesting with combine harvester. Thus, we conducted an exploratory study with a sample of 50 producers, which among its activities, cultivate beans in 11 cities of 3-regions of Paraná State. The survey consisted of questions referring to the bean crop, growing area, machine and adjustments used in the collection, quality of the product, making it possible to measure parameters determining the performance of the system of direct collection. Among the results highlight that the average productivity of the bean is above the state and national average. Decision-making for the choice of cultivar is based on commercial aspects related to grain color. About 40 of the cultivated varieties showed lodging index of 75 in the soil. Areas that are cultivated beans are major plan to gently undulating, depending on the operational performance of the harvester. The timing of the harvest is done by 44.93 of respondents across the uniformity of ripening. As to harvesters studied 100 are axial flow, formed by the special red bean. The settings for threshing, separation and cleaning of the grains are consistent with the recommendations of the manufacturer. During harvest 94 of the producers realize the direct sale of the material collected without any additional cleaning. The labor used in automotive harvesters receive little training. The adaptations found aims to improve the gathering of plants, the grain quality and reduction of mechanical damage.